Bialy oleander - Fitch, Janet, 1955- (Poznan : Zysk i S-ka, 2001)
Polish translation of "White Oleander". A Los Angeles girl whose mother goes to jail is taken in hand by the city's foster-care program and the novel describes her experience in a series of homes, each a new adventure.
Translation of: White oleander : a novel.
Keywords: Women murderers -- Fiction; Mothers and daughters -- Fiction; Foster children -- Fiction; Young women -- Fiction; Los Angeles (Calif.) -- Fiction